Living without God in a religious country: Polish nonbelievers as a cultural minority - Tyrala, Radoslaw (Social compass, 2018)
This article focuses on the community of Polish nonbelievers; according to different surveys, they constitute approximately 8% of the overall population. In this research-grounded opinion they should be treated as a minority, not only strictly numerically but also culturally, with all the consequences of this fact. This research conducted on the members of this group showed there are some important levels of such consequences. The first is the level of identity. The vast majority of my respondents were raised Catholic and therefore one may call them converts to non-religiousness. The second is the level of (non)religious consciousness. Less than one fifth of my respondents clearly expressed certain forms of religious belief, such as faith in an impersonal form of deity or in an afterlife. The third is the level of subjectively perceived discrimination. Polish nonbelievers rarely meet with direct expressions of prejudice against them during face-to-face encounters. However, they feel a strong social pressure to cultivate some elements of the ritual dimension of religiosity. At the end the author considers to what extent their minority status has a relative character.